Ortner's Syndrome: A cause of unilateral vocal cord paralysis - Vanitha Palanisamy; Kevin Suresh Doshi; Tengku Ezulia Tengku Nun Ahmad; Mohd Zulkifl ee Abu Bakar; Raman Rajagopalan (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2017)
Ortner's syndrome is rare syndrome characterised by hoarseness of voice due to recurrent laryngeal nerve involvement in cardiovascular disease.  This report presents a case of left laryngeal paralysis caused by an aortic arch aneurysm and to highlight the importance of an otorhinolaryngology evaluation along with a thoracic radiologic study.